ANALISIS STRATEGI BAHASA PERSUASIF PADA CAPTION PROMOSI UMKM DI INSTAGRAM DAN IMPLIKASINYA TERHADAP STRATEGI DIGITAL MARKETING - Sopyan Sapna; Mochamad Whilky Rizkyanfi; Yani Iriani (POLITEKNIK PIKSI GANESHA, 2026)
The rapid growth of social media has encouraged Micro, Small, and Medium Enterprises(MSMEs) to utilize Instagram as a marketing communication platform through promotionalcaptions containing persuasive language. However, studies on persuasive languagestrategies in MSME promotional captions and their implications for digital marketing remainlimited. This study aims to analyze the persuasive language strategies employed inInstagram promotional captions by MSMEs and examine their implications for digitalmarketing strategies. The research adopted a qualitative approach using qualitative contentanalysis. Data were collected through document analysis of 50 promotional captions from10 Instagram accounts of culinary MSMEs located in Jatinangor, Sumedang, and thesurrounding areas, selected using purposive sampling. The analysis was based on sixindicators: invitation statements, product superiority, promotional offers, urgency, call toaction, and emotional diction. The findings reveal that emotional diction was the mostdominant strategy (100%), followed by call to action (84%), invitation statements (80%), andproduct superiority (74%), while promotional offers (38%) and urgency (26%) were relativelyless utilized. In addition, the most frequently identified strategy combination consisted ofinvitation statements, product superiority, call to action, and emotional diction. This studyproposes a persuasive language strategy framework as a guideline for developing moreeffective MSME promotional captions to support digital marketing strategies. The findingscontribute to the advancement of digital marketing communication studies and providepractical guidance for MSMEs in developing more persuasive and effective promotionalcontent.Kata kunci : Persuasive Language, Promotional Captions, MSMEs, Instagram, DigitalMarketing